2017
DOI: 10.1103/physrevb.95.054511
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced intervortex interaction and vortex lattices in tetragonal superconductors

Abstract: In superconductors with strong coupling between superconductivity and elasticity manifested in a strong dependence of transition temperature on pressure, there is an additional contribution to inter-vortex interactions due to the strain field generated by vortices. When vortex lines are along the c axis of a tetragonal crystal, a square vortex lattice (VL) is favored at low vortex densities, because the vortex-induced strains contribution to the inter-vortex interactions is long range. At intermediate magnetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Stress builds up close to defects and modifies the superconducting length scales (and the Ginzburg-Landau parameter), producing an effective interaction between the crystal lattice and the vortex lattice 36,37 . Recently, it has been shown that stress induced intervortex interaction can lead to square vortex lattice in tetragonal superconductors 38 . Such a coupling between crystalline elasticity and superconductivity can be treated using the dependence of T c with pressure, dT c /dP 36,[39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Stress builds up close to defects and modifies the superconducting length scales (and the Ginzburg-Landau parameter), producing an effective interaction between the crystal lattice and the vortex lattice 36,37 . Recently, it has been shown that stress induced intervortex interaction can lead to square vortex lattice in tetragonal superconductors 38 . Such a coupling between crystalline elasticity and superconductivity can be treated using the dependence of T c with pressure, dT c /dP 36,[39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing, crucial aspects of our work are: (i) We establish RUS as a tool to not only give information about elasticity but also about dissipation mechanisms of the atomic lattice with high precision, sensitive to detect changes in the magneto-crystalline coupling that determines the orientation of the SKX (Note [29]). (ii) In analogy to superconducting vortices [30,31], the magnetocrystalline coupling in the SKX phase enables one to manipulate the skyrmions by external stress. (iii) Our work also reveals how the stability of the SKX phase changes as a function of its orientation with respect to the crystalline lattice.…”
mentioning
confidence: 99%
“…Theoretical approaches used to study structural transitions of the VL include modifications to the London model [17][18][19] , the addition of four-fold symmetric terms to the Ginzburg-Landau free energy 20 , Eilenberger theory 21 , modified Ginzburg-Landau approaches 22 , and modifications to the vortex interactions produced by strain fields 23 . Vortex lattice ordering can also be studied using molecular dynamics (MD) methods, which treat the vortices as point particles with bulk Bessel function interactions or thin film Pearl interactions.…”
Section: Introductionmentioning
confidence: 99%